2011
DOI: 10.7498/aps.60.038901
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of local structures in complex network:common neighborhood drives the network evolution

Abstract: After extensive study on the small-world and scale-free properties of networks, the research focus is shifting to detailed local structures. Empirical analysis shows that many real networks exhibit the power-law clique-degree distribution. This general regularity cannot be produced by the rich-get-richer mechanism. In this paper, we propose a common-neighborhood-dirven model in which the observed power-law clique-degree distribution con be well reproduced, indicating that the common-neighborhood-dirven mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…There is a modular structure in the network model proposed, modularity measure is proposed to describe the strength of module structure in a network. According to the Newman and Girvan's study [10] the network modular measure is expressed as…”
Section: Modularity Measurementioning
confidence: 99%
“…There is a modular structure in the network model proposed, modularity measure is proposed to describe the strength of module structure in a network. According to the Newman and Girvan's study [10] the network modular measure is expressed as…”
Section: Modularity Measurementioning
confidence: 99%
“…Therefore, betweenness provides a method of identifying intercommunity edges. [20,22] Figure 1 shows a graph with edge-betweenness labeled beside the edge.…”
Section: Betweenness and Community Detectionmentioning
confidence: 99%
“…Lü et al [19] suggested that in a network with large clustering coefficient, CN can provide competitively accurate predictions compared with the indices making use of global information. Very recently, Cui et al [20] revealed that the nodes with more common neighbors are more likely to form new links in a growing network. Simply counting the number of common neighbors indicates that each common neighbor gives equal contribution to the connection likelihood.…”
mentioning
confidence: 99%